Colonialism, Community, and Heritage in Native New England - Hart, Siobhan M., 1977- (Book collections on Project MUSE., 2019)
This book examines the relationships between community, politics, and heritage through an analysis of four Native American heritage landscapes in southern New England (Deerfield, Aquinnah, and Plimoth, Massachusetts and Mashantucket, Connecticut).